The relationship of human resource management practices on employee performance / Nurul Farhana Mohamed - Mohamed, Nurul Farhana (Faculty of Business and Management, 2018)
The purpose of this research was to investigate the relationship between Human Resource Management (HRM) Practices on employee performance at Perbadanan Kemajuan Negeri Melaka. There were three factors involved: training and development, employee involvement and performance appraisal and its influence on employee performance. The questionnaire were distributed to 150 staff of Perbadanan Kemajuan Negeri Melaka and the results analysed using SPSS. The results show that there is a relationship between training and development on employee performances, but not to employee involvement and performance appraisal.